Wear resistance of some modified ultra-high molecular weight polyethylenes and its correlation with tensile properties - Yim, CI; Lee, KJ; Jho, JY; Choi, KW (SPRINGER VERLAG, 1999)
Ultra-high molecular weight polyethylene (UHMWPE) was modified on purpose to enhance the wear resistance. The modification was done either by crosslinking the amorphous region of the surface using difunctional monomers or by crosslinking the bulk in the melt state using peroxide. The changes in thermal and tensile properties indicated that the modifications were effected. The volumetric wear rate, determined on a pin-on-disk wear tester, was suppressed by the modifications. The correlation between the tensile properties and the wear rates was sought. Any single tensile property or tensile rupture energy did not correlate well with the observed wear rate. Instead, the ratio of maximum contact stress calculated by the Hertz's contact theory to yield stress appeared to correlate well with volumetric wear rate.
Keywords: LINEAR POLYETHYLENE; DEFORMATION; MECHANISMS; POLYMERS; UHMWPE